Is the throne still for the people? A sociocultural linguistic analysis of Menanam adalah Melawan - Raden Safrina; Nita Novianti; Lina Meilinawati Rahayu (Studies in English Language and Education, 2024)
Tahta untuk Rakyat Throne for the People, which is the principle that the highly respected Hamengkubuwono IX lived by as a democratic and nationalist King of Kesultanan Ngayogyakarta Hadiningrat, embodies the concept of the people, by the people, for the people. Under his rule, Kesultanan Ngayogyakarta Hadiningrat (Yogyakarta Sultanate in Indonesia) was committed to placing the people first. Nevertheless, the book Menanam adalah Melawan, or Planting is Resisting, challenges the very principle and questions the commitment of the present-day sultanate. The article explores the activist book, which contains the notes of an activist farmer who reflected on and wrote about his journeys and experiences as a farmer-turned-activist after the village where he farmed was claimed by the authorities, including the sultanate, and was planned to be made into a mining site. Faircloughs sociocultural linguistics frames the analysis, and more specifically through Critical Discourse Analysis (CDA). The results indicate that at the micro level, Widodos writing uses emotive and technical language to construct a collective identity of marginalized farmers, opposing powerful entities like the sultanate and corporations. At the meso-level, the text challenges dominant power structures and neoliberal policies, advocating for social justice and a responsive monarchy, while emphasizing the need for transparency and genuine community partnership. The article indicates that the concern about the marginalized should take into account non-mainstream texts such as those produced by the marginalized so that social injustice can be minimized.